The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2265.2004.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dieting on plasma leptin, soluble leptin receptor, adiponectin and resistin levels in healthy volunteers

Abstract: These results demonstrate that a modest decrease in energy intake sustained over several weeks may play an important role in altering levels of plasma leptin and sOB-R. The findings also provide preliminary evidence that, in contrast to previous results in obese subjects, caloric restriction with accompanying weight loss in healthy, normal-weight volunteers may lead to decreased circulating adiponectin levels. Additional studies will be needed to clarify the contribution of altered energy intake to abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
87
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 50 publications
14
87
3
5
Order By: Relevance
“…In NGT subjects, adiponectinemia was slightly decreased with no change in insulin sensitivity. Although unexpected, this is in agreement with a recent study that reported a reduced adiponectinemia in healthy volunteers during a 4-week VLCD (11). It is interesting to note that, at the metabolic level, the NGT subjects were very close to non-obese subjects studied by Wolfe and colleagues (11).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In NGT subjects, adiponectinemia was slightly decreased with no change in insulin sensitivity. Although unexpected, this is in agreement with a recent study that reported a reduced adiponectinemia in healthy volunteers during a 4-week VLCD (11). It is interesting to note that, at the metabolic level, the NGT subjects were very close to non-obese subjects studied by Wolfe and colleagues (11).…”
Section: Discussionsupporting
confidence: 77%
“…Although unexpected, this is in agreement with a recent study that reported a reduced adiponectinemia in healthy volunteers during a 4-week VLCD (11). It is interesting to note that, at the metabolic level, the NGT subjects were very close to non-obese subjects studied by Wolfe and colleagues (11). Therefore, as previously suggested, it can be hypothesized that the predominant loss of S.C. instead of visceral adipose tissue could explain the decrease in adiponectin level.…”
Section: Discussionsupporting
confidence: 76%
“…Some investigators observed a decrease in serum resistin during weight loss 5,10 or an increase during weight gain, 32 while others reported no changes in serum resistin. 33,34 In the present study, serum resistin was positively correlated to serum fructosamines and HOMA-SI. Nevertheless, favorable changes in markers of glucose metabolism and insulin resistance during weight loss were not related to changes in serum resistin during the intervention.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, the effect of exercise on adiponectin levels in obesity may be different between male and female subjects. Adiponectin levels have been reported to be inversely correlated with central adipose tissue stores [34,35] and positively correlated with subcutaneous adipose tissue [36]. Thus, it is possible that loss of visceral fat has resulted in increased adiponectin levels concomitante with body weight reduction in obese young women in the present study.…”
Section: Discussionmentioning
confidence: 50%